CAPABILITIES OF THE GOVERNMENT INTERNAL SUPERVISION APPARATUSF AT THE REGIONAL INSPECTORATE OF SOUTH SULAWESI PROVINCE - Sakawati, Herlina; Hiyar, Annisa Nurul Hasanah; Akib, Haedar (Universitas Negeri Makassar, 2024)
This research aims to find out the capabilities owned and supervision at the Regional Inspectorate of South Sulawesi Province. This research is a qualitative research that shows an objective picture of a situation. Data collection was carried out through observation, interview, and documentation techniques. The data analysis techniques used in this study are data reduction, data presentation, and conclusion drawn.The results of the study show that the APIP Capability at the Regional Inspectorate of South Sulawesi Province has been running well, although there are still some shortcomings in its implementation. This can be seen from Roles and Services, Professional Practices, Accountability and Performance Management, Culture and Organizational Relationships, Structure and Governance that have been running well, but there are still shortcomings in HR Management. The supervision carried out as a form of service for ASN is the Review Assistance Service for Regional Apparatus Organizations (OPD) in the South Sulawesi Provincial Government, the Digitization System for Follow-up Information on Audit Results (TLHP), Submission of Complaints of Suspected Criminal Acts and Violations of ASN Discipline.